An Electrochemical Biosensor with Uricase Immobilized on Functionalized Gold Coated Copper Wire Electrode for Urinary Uric Acid Assay. Issue 4 (14th October 2015) - Cheng, Cheanyeh; Kao, Chi‐Ying
Abstract: A new second generation uricase electrode for urinary uric acid determination has been developed by chemically binding both uricase and redox mediator to inexpensive copper wire through simple electrodeposition of gold on copper surface and subsequent functionalization of the gold with L‐methionine. During a 209‐day testing period, the overall electrode performance exhibits in average a low oxidation potential of 0.33 V, a response time of 5 s, a widest linear calibration concentration range (0–2.38 mM, r 2 >0.9952), a sensitivity of 50 μA mM −1, and a detection limit of 2.4 μM. The measurement accuracy and precision for the determination of uric acid in human urine specimens were 85.6–95.5 % and 0.3–2.4 %, respectively. The developed uricase electrode is potential for clinical applications. Abstract :